Exploring Culturally Responsive Teaching (CRT) On Poetry And Drama Class - Ibrahim, Muhammad Bagus; saifulloh, Ahmad Iklil; Mardiana, Wiwik (PT. Kreasi Karya Majakata, 2024)
This paper discusses the practice of Culturally Responsive Teaching in a